The Impact of population growth on socio-economic development - Ahmad, Afzaal (KDI School, 2011)
Pakistan is the sixth by virtue of its population size. This colossal population and galloping population growth rate consumes most of financial and natural resources and leaves little for development. The population growth is a challenge posed to Pakistan economy as it increases expenditures on health, education infrastructure and basic provisions of life. It also depletes natural resources, food, water etc. Development is the center of all economic activities. However, development alone is futile when it does not bring positive change in the lives of masses. Different studies have shown that population growth negatively affects development process. In the backdrop of Pakistan, this situation has been worsened as the problem was never given due attention and gravity of the problem with its multi-dimensional facets has become very complicated. Despite limited possible government efforts, the fertility rate has not decreased to the stabilized population growth rate at desirable level. The huge population size deprived of health care, education and employment facilities is a titanic load over the poorly managed economy growing at snail pace. The empirical analysis done in this thesis supports the hypothesis, that population growth is negatively related to factors involved in sustainable economic development.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Pakistan.